5-HT7 Receptor Inhibition Transiently Improves Respiratory Function Following Daily Acute Intermittent Hypercapnic-Hypoxia in Rats With Chronic Midcervical Spinal Cord Contusion. (April 2020) - Wu, Ming-Jane; Vinit, Stéphane; Chen, Chun-Lin; Lee, Kun-Ze
Background . Intermittent hypoxia can induce respiratory neuroplasticity to enhance respiratory motor outputs following hypoxic treatment. This type of respiratory neuroplasticity is primarily mediated by the activation of Gq-protein-coupled 5-HT2 receptors and constrained by Gs-protein-coupled 5-HT7 receptors. Objective . The present study hypothesized that the blockade of 5-HT7 receptors can potentiate the effect of intermittent hypercapnic-hypoxia on respiratory function after cervical spinal cord contusion injury. Methods . The ventilatory behaviors of unanesthetized rats with midcervical spinal cord contusions were measured before, during, and after daily acute intermittent hypercapnic-hypoxia (10 episodes of 5 minutes of hypoxia [10% O2, 4% CO2, 86% N2 ] with 5 minutes of normoxia intervals for 5 days) at 8 weeks postinjury. On a daily basis, 5 minutes before intermittent hypercapnic-hypoxia, rats received either a 5-HT7 receptor antagonist (SB269970, 4 mg/kg, intraperitoneal) or a vehicle (dimethyl sulfoxide). Results . Treatment with intermittent hypercapnic-hypoxia induced a similar increase in tidal volume between rats that received SB269970 and those that received dimethyl sulfoxide within 60 minutes post-hypoxia on the first day. However, after 2 to 3 days of daily acute intermittent hypercapnic-hypoxia, the baseline tidal volumes of rats treated with SB269970 increased significantly. Conclusions . These results suggest that inhibiting the 5-HT7 receptor can transiently improve daily intermittent hypercapnic-hypoxia–induced tidal volume increase in midcervical spinal contused animals. Therefore, combining pharmacological treatment with rehabilitative intermittent hypercapnic-hypoxia training may be an effective strategy for synergistically enhancing respiratory neuroplasticity to improve respiratory function following chronic cervical spinal cord injury.